The Effect of Implementing an Interactive Thermodynamics E-Module Based on Collaborative Teamwork Learning Using Quizzes on the Learning Outcomes of Grade XI Students at MAN 3 Muaro Jambi - Loviya, Mesi; Purwaningsih, Sri; Huda, Nizlel (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
This study aims to determine the effect of implementing an interactive e-module on the Thermodynamics material, developed using Collaborative Teamwork Learning and supported by quizzes, on the learning outcomes of Grade XI students at MAN 3 Muaro Jambi. The research method used is a quasi-experimental pretest-posttest control-group design. The research sample consisted of two classes: the experimental class, which used the interactive e-module, and the control class, which used conventional learning methods. The instrument used in this study was a learning outcome test validated by experts. Data analysis was conducted using the Mann-Whitney U test in SPSS to determine differences in learning outcomes between the two groups. The test results showed a significance value (Asymp. Sig. 2-tailed) of 0.000 0.05, indicating that the null hypothesis (H₀) was rejected. This shows a significant difference in learning outcomes between the experimental and control classes. Students who learned using the interactive e-module, supported by Quizizz, showed greater improvement in learning outcomes than those in the control class. These findings indicate that the use of an interactive e-module with a collaborative approach and reinforcement through quizzes can significantly enhance students' understanding of Thermodynamics concepts.